2020
DOI: 10.1194/jlr.ra120000898
|View full text |Cite
|
Sign up to set email alerts
|

Locations and contributions of the phosphotransferases EPT1 and CEPT1 to the biosynthesis of ethanolamine phospholipids

Abstract: The final step of the CDP-ethanolamine pathway is catalyzed by ethanolamine phosphotransferase 1 (EPT1) and choline/ethanolamine phosphotransferase 1 (CEPT1). These enzymes are likely involved in the transfer of ethanolamine phosphate from CDP-ethanolamine to lipid acceptors such as 1,2-diacylglycerol (DAG) for phosphatidylethanolamine (PE) production, and 1-alkyl-2-acylglycerol (AAG) for the generation of 1-alkyl-2-acyl-glycerophosphoethanolamine (plasmanyl-PE). Here, we investigated the intracellular locatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 26 publications
2
34
0
Order By: Relevance
“…PE synthesis is dependent to a lesser extent, mainly during T activation. T cells appear to be able to compensate for the loss of SELENOI to maintain levels of total PE (unlabeled and labeled), similar to recent studies using HeLa and HEK293 cell lines [ 34 , 35 ].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…PE synthesis is dependent to a lesser extent, mainly during T activation. T cells appear to be able to compensate for the loss of SELENOI to maintain levels of total PE (unlabeled and labeled), similar to recent studies using HeLa and HEK293 cell lines [ 34 , 35 ].…”
Section: Resultssupporting
confidence: 80%
“…SELENOI is a versatile enzyme participating in two phospholipid synthesis pathways: it may transfer the ethanolamine headgroup from CDP-ethanolamine to either DAG or AAG to generate PE or plasmenyl PE, respectively. Although SELENOI participates in the biosynthesis of both, data from HeLa and HEK293 cell lines suggested that, in the absence of SELENOI, mainly plasmenyl PE levels are reduced since cells can utilize choline/ethanolamine phosphotransferase 1 (CEPT1) to maintain PE synthesis [ 34 , 35 ]. Our results suggest that the same is true for T cells as only plasmenyl PE in the labeled and unlabeled forms were lower in the SELENOI KO T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of function of EPT1 may be able to be compensated for, in part, by the presence of CEPT1, although this remains to be established. To this end, knockdown of EPT1 or CEPT1 in HEK293 cells resulted in viable cells [49], with metabolic labeling analyses revealing that EPT1 preferentially synthesized plasmenyl-PE and PE species with long chain unsaturated fatty acids, whereas CEPT1 preferentially synthesized diacyl-PE with shorter and more saturated fatty acids [49]. Similarly, analysis of cells derived from EPT1 HSP patients determined that the total level of PE was similar to controls, however, PE species with polyunsaturated fatty acids were reduced [47,48].…”
Section: Mutations In Pcyt2 and Ept1 For Pe Synthesis Cause Inheritedmentioning
confidence: 99%
“…Although we do not know the precise mechanism of this additional layer of co-regulation, the increase in C16 SLs or the decrease in C24 SLs might affect the activity of enzymes adding head groups on ether DAG, either by reducing the transfer of phosphocholine or increasing the transfer of phosphoethanolamine ( Figure 6E). Interestingly, an enzyme catalyzing the transfer of the phosphoethanolamine head group, ethanolamine phosphotransferase 1 (EPT1, encoded by SELENOI gene), is localized to the Golgi apparatus [33], where the biosynthesis of complex SLs takes place. This enzyme is more important for ether PE synthesis than for PE synthesis, and has a preference for substrates containing PUFAs [34].…”
Section: Dissection Of Co-regulatory Network With Multiplex Genfmentioning
confidence: 99%